1997
DOI: 10.1111/1467-9523.00033
|View full text |Cite
|
Sign up to set email alerts
|

From Farm to Table: The Organic Vegetable Commodity Chain of Northern California

Abstract: Farmers and consumers 'marginal' to the industrial agro-food system occupy the interstices of this network . . . (t)hese tangential spaces represent sites of alternative strategies which build on traditional production practices centred on subsistence and 'informal' market networks, or are bound up with new social movements associated with non-agridturd or non-food issues. (Whatmore 1995, p. 47) The social basis for a democratic food policy lies in movements for employment and incomes, for safe and nutritio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
382
3
32

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 434 publications
(421 citation statements)
references
References 8 publications
4
382
3
32
Order By: Relevance
“…The speed at which this occurs may be surprising to those involved in creating agrifood alternatives. In organics, for example, corporate participation increased dramatically in the mid1990s as the organic sector approached 1% of total U.S. food sales, and just as progress toward a uniform federal standard was being made (Buck et al 1997;Obach 2007). Appropriation of the discourse of ''local'' food occurred even faster (Wal-Mart 2006;Novak 2008).…”
Section: The Motive Of Accumulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The speed at which this occurs may be surprising to those involved in creating agrifood alternatives. In organics, for example, corporate participation increased dramatically in the mid1990s as the organic sector approached 1% of total U.S. food sales, and just as progress toward a uniform federal standard was being made (Buck et al 1997;Obach 2007). Appropriation of the discourse of ''local'' food occurred even faster (Wal-Mart 2006;Novak 2008).…”
Section: The Motive Of Accumulationmentioning
confidence: 99%
“…The extent to which this has occurred is demonstrated by the fact that 14 of the 20 largest food processors in North America have either acquired organic brands or introduced organic versions of their existing brands (Howard 2009). There is also evidence that organic farms are increasing in scale and using more capital intensive inputs and production techniques, although the wide applicability of the ''conventionalization thesis'' to areas outside California is debated (Buck et al 1997;Guthman 2004b;Lockie et al 2006). Table 1 lists significant events that have occurred in the organic industry and regulatory framework since the national standard was implemented, that movement-oriented participants have claimed are examples of cooptation (column C).…”
Section: Standards Cooptation In Organicsmentioning
confidence: 99%
“…On the other hand, it has also been shown that organic agriculture is capable of feeding the world sustainably , especially if farming practices that mitigate climate change are also sufficiently employed (Badgley and Perfecto 2007;Scherr and Sthapit 2009). In considering the market of organic food, however, fundamental contradictions have been identified between mainstream agro-industrial and alternative movement conventions, because increases in scale and standardization lead to the bifurcation of the organic sector and the watering down of its original values (Buck et al 1997;Constance et al 2008). Thus, a globalizing organic agro-food sector risks susceptibility to similar ills it aimed to cure in the first place (Raynolds 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The actual research of this issue was initiated more than 10 years ago, discussed in publications of Tovey (1997) and Buck et al (1997). These authors were the first to point out that the growing organic sector could turn out to be similar to the industrial agriculture that it has traditionally opposed, therefore undermining the intrinsic values of organic ideology.…”
Section: Introductionmentioning
confidence: 99%
“…Campbell et al (2001, p. 23) argue that this situation stems from the theoretical approach of the early conventionalization works (namely by Buck et al 1997) which appeared to excessively emphasize the commoditization, or corporatization process, which then from this viewpoint inevitably transformed small artisanal organic producers into managers of large industrial farms. The dichotomous perspective wrought by the conventionalization thesis was also criticized by Lockie et al (2005, p. 304), who observing the tendency to bifurcate, highlighted the need to first "unpack" the concept of conventionalization, and to extend the debate over the development of organic farming.…”
Section: Introductionmentioning
confidence: 99%